HISTOMOIlPlfQi^OGY OF THE TASTE RECEPTORS OF SOME FRESHWATER FISHES - Kulshreshta, S D (Indian Journal of Fisheries, 2011)
The taste receptors or buds are ovoid clusters of modified epithelial cells which are embedded in the:s^fttifled epithelium of various organs. They are distinct frcmi the neuromast organs of the lateral-line system and, accordingly, Walter (1928) has named the tate receptors as gustoreceptors and the neuromast organs as rheoreceptors